TELEVISION IN THE POETRY OF VICTOR KRIVULIN / ТЕЛЕВИДЕНИЕ В ПОЭЗИИ ВИКТОРА КРИВУЛИНА - MARKOV ALEXANDER V. / МАРКОВ А.В. (Наука телевидения)
The paper explores the representation of television and the television screen in the later poetry of Viktor Krivulin (1944–2001), a prominent figure in independent Russian literature. The analysis is framed within the concept of the underground culture, which highlights a creative individual’s media engagement, as well as media selection based on credibility, message relevance, and replicability. It is hypothesized that this experience significantly influenced Krivulin’s depiction of television. The study evaluates the utility of Lacan’s methodology, as interpreted in Kittler’s media theory,for analyzing Krivulin’s poems. The world he portrays is consistently one of historical devastation, where television often serves to obscure reality. However, the nature of news changes in the post-Soviet era: it is no longer cultural updates, but news from the world of media, with a peculiar self-destructive language. Not only television shapes news presentation; it also influences modes of existence in front of and behind the screen, which could be compared to pre-mortem and post-mortem states following the collapse of the culture’s symbolic body. In Krivulin’s work from the 1990s, the portrayal of television as a broadcasting medium undergoes several transformations, influenced by shifts in artistic objectives and changes in television stylistics during this period. The paper delineates a timeline of these shifts and identifies a common trajectory in this evolution. Initially perceived as an innovative force building new social and political connections between generations, television later transitioned into a part of everyday life during a period of significant change and the disruption of previous social connections between people and their former media provisions. Eventually, television began to be viewed as a distinct form of information delivery, akin to theater and dreaming, heralding a positive narrative of historical memory. At all stages, television is contrasted with radio broadcasting as the notification of a catastrophic disaster. В статье рассматривается образ телевизора и телевизионного экрана в поздней поэзии Виктора Кривулина (1944–2001), одного из самых ярких поэтов независимой русской литературы. Рамкой рассмотрения стало понятие второй (катакомбной, андеграундной) культуры, подразумевающее прежде всего медийную активность творческого человека, выбор медиа в зависимости от достоверности, актуальности сообщения и возможности тиражирования. Выдвигается гипотеза, что этот опыт решительно повлиял на возникновение в творчестве Кривулина образа телевидения. Показана продуктивность методологии Жака Лакана, воспринятой в теории медиа Фридриха Киттлера, для анализа стихотворений Кривулина. Мир, который изображает Кривулин — это всегда мир исторической разрухи, где телевидение скорее маскирует ситуацию. Но в постсоветское время меняется понимание того, что такое новости: это уже не новости культуры, а новости из мира медиа, со своеобразным саморазрушающимся языком. Телевидение при этом регламентирует как способ подачи новостей, так и режимы существования перед экраном и за экраном, которые могут быть сопоставлены с режимами предсмертного и посмертного существования после разрушения символического тела культуры. В творчестве Кривулина 1990-х образ телевизора как вещания неоднократно трансформировался, в зависимости и от изменения художественной задачи, и от перемен стилистики самого телевидения в эти годы. В статье выстраивается хронология таких перемен и их общий вектор, проходящий через все творчество Кривулина. Сначала телевидение воспринималось как новация, иначе строящая отношения между политической культурой поколений. Потом телевидение превратилось в часть быта, в период больших перемен и разрушения и прежних связей между людьми, и прежнего их медийного обеспечения. Наконец, телевидение начинает восприниматься как особый стиль информирования, сопоставимый с театром и сновидением, и утверждается программа исторической памяти как положительного действия. При этом на всех этапах телевидение противопоставляется радиовещанию как извещению катастрофического бедствия.